Konsep Jiwa dan Tubuh Manusia Menurut St. Maximos The Confessor Kebajikan Jiwa dan Tubuh Manusia Menuju Pengilahian - Ririn Valentina Halawa; Hendi Wijaya (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2023)
According to Idealistic and Materialistic Opinions, body and spirit are diametrically opposed. The body is the visible physical component of a person, while the soul is the invisible, inner component. While the soul is an essential component of all living things, the body is a connection of substances that serves as the unique basis of the physical body capable of life. According to Maximos, the divine capacity correlates with God becoming human through his love for humans. This study aims to show how the virtues of the human body and soul can approach divinity. This research work uses literature review as its methodology, with the book